A general polling algorithm using a wireless AMR system for restoration confirmation. - Fischer, R.A (IEEE Transactions on power systems)
Restoration of distribution systems is a complicated process, especially after storms, when a large number of outages can occur. Many utilities are implementing automated meter reading (AMR) systems that can aid in the restoration process. This paper presents work done to utilize the capabilities and information provided by a wireless AMR system, including the on-demand read feature, to develop a polling procedure to identify system conditions. It takes advantage of the connection information provided by a utility and the performance of the wireless meter communication systems